Conservative Turn and Islamic Populism: Challenges Muhammadiyah and Nahdlatul Ulama in Contemporary Politics - Qodir, Zuly; Singh, Bilveer; W. Hefner, Robert (UIN Sunan Gunung Djati Bandung, 2023)
This article objectives explore the main challenges of Indonesian democracy after the 2019 presidential election, namely the revival Islamic conservatism and populism, which seem to have seamlessly integrated into the Indonesian political praxis. This article to the authors attempt to the Muhammadiyah and Nahdlatul Ulama response rise the conservatism and Islamic populism contextualizing the contemporary democratic politics in Indonesia. This article uses a qualitative writing method by taking data from articles written by previous authors from journals that have been published according to the topic of this article after the 2019 election took place. The issue of conservatism, and Islamic populism will continue to develop if the moderate Islamic forces of Muhammadiyah and Nahdlatul Ulama (NU) do not rise to the occasion in Indonesia’s political and religious life. After all, the country’s democratic life depends invariably on the maintenance of civility and the non-discriminative nature of the Islamic agenda held dearly by the two influential organizations. Should the moderate forces of Indonesian Islam weaken, then conservatism and populism would no doubt prevail. This article objectives explores the main challenges of Indonesian democracy after the 2019 presidential election, namely the revival Islamic conservatism and populism, which seem to have seamlessly integrated into the Indonesian political praxis. Conservatism and populism in Indonesian politics nothing useful in grassroots but only in the political elite. In this article objectives to the authors attempt to the Muhammadiyah and Nahdlatul Ulama response rise the conservatism and Islamic populism contextualizing the contemporary democratic politics in Indonesia. This study recommends that the study of Islamic populism in relation to Indonesian politics after the 2019 election be an expanded study in terms of network and actor issues. So that a new role was found that contributed to the populism movement in Indonesia.